Enhancing Buoyant force learning through a visuo-haptic environment: a case study - Neri, Luis; Noguez, Julieta; Escobar-Castillejos, David; Robledo-Rella, Víctor; García-Castelán, Rosa María Guadalupe; Gonzalez-Nucamendi, Andres; Magana, Alejandra J.; Benes, Bedrich (Frontiers in Robotics and AI, 2024)
Introduction: This study aimed to develop, implement, and test a visuo-haptic simulator designed to explore the buoyancy phenomenon for freshman engineering students enrolled in physics courses. The primary goal was to enhance students’ understanding of physical concepts through an immersive learning tool.Methods: The visuo-haptic simulator was created using the VIS-HAPT methodology, which provides high-quality visualization and reduces development time. A total of 182 undergraduate students were randomly assigned to either an experimental group that used the simulator or a control group that received an equivalent learning experience in terms of duration and content. Data were collected through pre- and post-tests and an exit-perception questionnaire.Results: Data analysis revealed that the experimental group achieved higher learning gains than the control group (p = 0.079). Additionally, students in the experimental group expressed strong enthusiasm for the simulator, noting its positive impact on their understanding of physical concepts. The VIS-HAPT methodology also reduced the average development time compared to similar visuo-haptic simulators.Discussion: The results demonstrate the efficacy of the buoyancy visuo-haptic simulator in improving students’ learning experiences and validate the utility of the VIS-HAPT method for creating immersive educational tools in physics.